A Prediction Model for Concrete Cracks due to Chloride-Induced Corrosion - Jiao Wang; Ling Li; X. G. Zhang; Yangang Zhao (Advances in Materials Science and Engineering)
The nonhomogeneity of concrete leads to randomness in the development and extension of cracks. Scholars have proposed different models to analyze the development of cracks. Different from existing works on crack development, in this paper, we establish a crack spacing model on the basis of the mechanical equilibrium relation of differential elements. We also establish a mechanical equilibrium model considering that the shrinkage of concrete is constrained by the bonding force of reinforced concrete. Then, on the basis of the equilibrium condition, we propose an analytical model of spacing between the first crack and the second crack at the interface of steel and concrete due to corrosion expansion. This calculation model has only three variables: tensile strength, effective constraint length of the reinforcement, and bond force. In addition, the parameters are clearly defined. We verified the development of cracks at the interface between steel bar and concrete under chloride corrosion at different locations in a steel bar by comparing it with existing simulations and experimental results. The analytical model proposed in this paper has an accuracy of 92%, indicating that our expression for crack spacing can effectively predict the location of cracks.